No Pain, No Gain? Personality Associations With Awareness of Aging Depend on Arthritis - Dunsmore, Victoria J.; Neupert, Shevaun D. (Frontiers in Psychology, 2022)
Background: Awareness of aging brings to light one’s own perceived behavioral, physical, and cognitive changes associated with getting older. Personality and physical illness are each related to two components of awareness of aging: attitudes towards own aging (ATOA), and awareness of age-related changes (AARC). Here, we move beyond main effects to examine how personality and arthritis interact with respect to awareness of aging. Method: 296 participants (M age = 64.67, SD = 4.36, Range = 60-90 years, 49.7% women) completed online self-report questionnaires of personality, arthritis, ATOA, and AARC gains and losses. Results: We ran 3 hierarchical multiple regression models to test how personality traits and arthritis interacted to predict ATOA, AARC gains, and AARC losses, respectively. Higher extraversion was related to positive ATOA, and higher openness was related to positive ATOA and more AARC gains. Higher neuroticism was related to negative ATOA, more AARC losses, and less AARC gains. We found a main effect for arthritis, where those with arthritis reported more AARC losses. Lastly, we found a significant interaction between arthritis and agreeableness when predicting AARC gains. Among those with low agreeableness, people with arthritis reported significantly more AARC gains compared to those without arthritis. Conclusions: Personality and arthritis are each important for awareness of aging. Overall, our study suggests that for those with arthritis, it is especially important to consider behavioral and cognitive factors related to agreeableness, as they may be important means of promoting positive views on aging.